2021
DOI: 10.24251/hicss.2021.334
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Consumer Perception of Online Review Helpfulness: Synthesizing the Past to Guide Future Research

Abstract: A growing body of academic research has aimed to investigate the helpfulness of online customer reviews (OCRs) given their prevalence and the need to better understand their appraisal mechanisms. However, past studies have applied varied methods and reported conflicting findings. This study aims to improve the understanding of the contributors to OCR helpfulness by synthesizing past studies on the topic. Based on a systematic literature review, a summary of the precursors to OCR helpfulness is provided. We dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
4
0
1
Order By: Relevance
“…Positive and negative sentiments' role in shaping online review helpfulness is less straightforward. Indeed, previous studies have reached conflicting conclusions about this role (Fan, 2021; Lee et al , 2017; Salehan and Kim, 2016; Siering and Muntermann, 2013). For instance, Lee et al (2017) demonstrated that negative reviews are considered more helpful than positive reviews.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Positive and negative sentiments' role in shaping online review helpfulness is less straightforward. Indeed, previous studies have reached conflicting conclusions about this role (Fan, 2021; Lee et al , 2017; Salehan and Kim, 2016; Siering and Muntermann, 2013). For instance, Lee et al (2017) demonstrated that negative reviews are considered more helpful than positive reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Star ratings' quadratic terms were included to account for the nonlinear relationship between rating and helpfulness (Mudambi and Schuff, 2010). Readability was calculated using the automated readability index (Smith and Senter, 1967), a method of determining written material's difficulty (Fan, 2021; Korfiatis et al , 2012). The operationalization of the variables used in this study is presented in Table 4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Milyonlarca tüketici, satın alma kararları için diğer tüketiciler tarafından üretilen derecelendirme ve yorumları değerlendirmekte ve bunlara güvenmektedir (İktisadi İş birliği ve Gelişme Teşkilatı [OECD], 2019, s. 6). Çevrimiçi tüketici yorum ve incelemeleri; ticari olmayan nitelikleri, içeriklerinin zenginliği ve tüketicilerin karar alma süreçlerine olan etkisi nedeniyle önem kazanmıştır (Fan, 2021(Fan, , s. 2738. Senecal ve Nantel'in (2004, s. 167) ifade ettiği üzere, çevrimiçi değerlendirme kaynaklarının tüketicilerin seçimlerini etkileyebilecek ürünleri tavsiye ettiklerinde söz konusu ürünlerin iki kat oranında daha fazla tercih edildiği bilinmektedir.…”
Section: Introductionunclassified